Sexuality and the Dimensions of Power - Brickell, Chris (Sexuality & Culture : An Interdisciplinary Quarterly, 2009)
Power, many scholars agree, is intrinsic to the relationships between sexuality, individual experience and social dynamics. Beyond this basic agreement, though, writers and researchers have adopted different foci. This article critically reviews several approaches to the power-sex relationship, and suggests that four readily discernable but interlaced dimensions of power operate upon the sexual: definitional, regulatory, productive and unequal. As a number of examples from the literature show, these ideal typical forms twist and interweave in both theory and practice. I suggest that to be mindful of all four facets of power and their interrelationships is to account for multiplicity, and to avoid the reductive characterizations that have sometimes characterized academic writings on power and sexuality. In this way, both theory and research in the area of human sexuality can be more thoroughly conceptualized.
Keywords: approches et analyses; cours; discipline; hétérosexisme; premier cycle; queer; rapports de pouvoir; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Hopeless love: Boiardo, Ariosto, and narratives of queer female desire - DeCoste, Mary-Michelle (Toronto Italian studies, 2009)
Le troisième livre du poème épique du poète italien Matteo Maria Boiardo, Orlando innamorato (Orlando amoureux), a été publié à titre posthume en 1494 ; en 1532, le poète Ludovico Ariosto publie sa version finale d'une suite, Orlando furioso (La Frénésie d'Orlando). À la fin de son poème, Boiardo raconte l'histoire du désir insatisfait de la princesse Fiordispina pour la jeune guerrière Bradamante, une histoire que l'Arioste raconte dans le corps de son œuvre ultérieure. Dans Hopeless Love , Mary-Michelle DeCoste examine les deux versions de l'épisode Fiordispina et Bradamante en utilisant la théorie féministe et queer. DeCoste relie ensuite ces traitements du désir féminin queer à leurs contextes culturels plus larges en explorant leurs antécédents dans des genres tels que l’épopée romantique médiévale et l’hagiographie et en examinant des tropes similaires dans d’autres épopées romantiques du XVIe siècle. Œuvre importante sur un sujet jusqu'alors négligé, Hopeless Love révèle la diffusion du désir féminin queer dans la littérature italienne et promeut une meilleure compréhension de la sexualité dans l'Europe médiévale et de la Renaissance.
Keywords: 1500-1599; approches et analyses; europe; identités LGBTQIA2+; italie; personnes lesbiennes; périodes historiques; queer; ressource en ligne; régions géographiques; sexualité; thématiques

Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

The emotions least relevant to politics? Queering autonomous activism - Wilkinson, Eleanor (Emotion, Space and Society, 2009)
Studies of emotion and activism have often attempted to uncover ‘the emotions most relevant to politics’ (Goodwin et al., 2001). This suggests that only certain feelings are productive for activism, while other emotions have less relevance for activist theory and practice. In this paper I ask if the notion of politically ‘relevant’ emotions helps perpetuate a distinction between what is considered political and what is not. This paper builds upon a case study in which I interviewed self-identified queer-activists about their experiences of autonomous activism. These interviews reveal how the everyday emotions surrounding the ‘personal’ politics of sexuality/intimacy are often seen as either less important, a distraction from, or entirely irrelevant to ‘real’ political issues. Ultimately, I want to challenge attempts to neatly separate our intimate lives from the public sphere of activism. I argue that it can never just be a matter of politics and emotion, but also the politics of emotion (Ahmed, 2004). Therefore we should not just assume that emotions matter for resistance - without first realizing the importance of resisting these hierarchies of emotion.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; europe; militance; périodes historiques; queer; ressource en ligne; royaume-uni; régions géographiques; sexualité; thématiques; émotions; étude qualitative

On ne naît pas femme - Wittig, Monique (La pensée straight, 2009)
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; fem1000; lesbianisme; pol4212; politique; premier cycle; périodes historiques; queer; sexualité; thématiques; théories féministes